Epidemiology of tennis injuries: An eight-year review of Davis Cup retirements - Maquirriain, J.; Baglione, R. (European Journal of Sport Science, 2016)
Tennis practice, especially at elite levels, may place players at risk for debilitating musculoskeletal injuries. The aim of this study was to analyse the epidemiological pattern of retirements due to medical conditions sustained by tennis players during Davis Cup matches in the 2006-2013 period. All uncompleted matches due to a medical condition (injuries and illnesses) occurred in the above-mentioned competition were collected from the official source, registered and analysed according to published guidelines. The overall incidence of match retirements was 1.66% (12/719). The injury rate was 6.05/1000 playing hours; and 6.64/1000 match exposures. Musculotendinous lesions were the most common type of injury (66.66%). The incidence of lower-limb injuries was higher than upper-limb and trunk lesions. The incidence of retired matches due to medical conditions was higher in hard courts than in clay courts (2.97% and 0.90%, respectively; p = 0.04), while the median value of inactivity of injuries was 32.0 days (range 3-297). In conclusion, the incidence of retirements due to medical conditions in Davis Cup matches was low supporting the assumption that elite tennis is a low-risk sport activity. Findings provided scientific evidences of injury patterns among male professional tennis players and may contribute to conduct better injury prevention strategies.